Test Questionnaire «Partial Positions of Personality Hardiness»: Results of Creation and Approbation - Brynza, Iryna; Kuznetsova, Oksana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents the theoretical construction, stages of creation and results of psychometric verification of the test questionnaire «Partial positions of personality hardiness» (PPH). Hardiness stands for the ability of an individual to assimilate experience and development during life’s difficulties. Partial positions of personality hardiness cover a specific manifestation of the characteristics in different types of hardships, which is implemented in a range of emotional reactions and feelings, the nature of psychological difficulties, mechanisms of assimilation of problem experience, coping strategies and transformation of unpleasant circumstances.The developed test questionnaire contains 100 statements, distributed on 5 scales of 20 statements each: «hardiness in a situation of stress», «hardiness in a situation of frustration», «hardiness in a situation of conflict», «hardiness in a crisis», «resilience in situations of uncertainty». The algorithm of the original method construction provided for several stages that meet the requirements of modern psychometrics. At the stage of approbation of the test questionnaire its reliability (method of division in half, parallel test, check of independence of results from the personality of the diagnostician), obvious, constructive, convergent; competitive validity (methods of correlation, factor analysis), discriminativeness has been verified. The presence of correlations between the indicators of the PPH test questionnaire and the S. Muddy Test of hardiness (adapted by D. Leontiev, O. Rasskazova) indicates that the developed method measures the same psychological quality as the reference test, but low (from 0.20 to 0.30) and average (from 0.30 to 0.50) values of correlation coefficients indicate that the new method has different theoretical construction grounds. Comparison of data between the test-questionnaire of PPH and parallel tests («Test-questionnaire of indicators` diagnostics of psychological crisis experience» (PE) (O. Sannikova, I. Brynza), and a method of «Self-assessment of mental states according to G. Eysenck») showed existence of negative correlations between of the majority of comparative methods` indicators of (p≤0.01; p≤0.05).The results of approbation approved the conformity of the created method in accordance with psychometric requirements, which allows to use it both for scientific and practical purposes.
Keywords: hardiness; stress situation; frustration situation; crisis situation; conflict situation; uncertainty situation; psychometric indicators